What can artificial intelligence do for tennis? - Vives, F. (Coaching and Sport Science Review, 2024)
In the current era of Artificial Intelligence, we are witnessing how this technology is revolutionizing the world of sports. Through a review of the main Machine Learning research in tennis over the last decade, players, coaches, and fitness trainers can discover new proposals to improve and personalize training sessions, enhance player effectiveness, and optimize decision-making during competition.